THE URGENCY OF SUNNI TASAWUF OF K.H. AHMAD SANUSI IN TATAR SUNDA: A STUDY OF SIRĀJ AL-AŻKIYĀ’ FĪ TARJAMAH AL-AZKIYĀ’ - Tsamrotus Saadah, Rifa; Mumtaz Ali, Zaky (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT This article focuses on Sanusi's journey in promoting Sunni Sufism through his book Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’ in the Sukabumi region of West Java. In his book, Sanusi not only focuses on Dakwah but also strengthens his position as a Sundanese ajeng who influences the way of Sunni Sufism in Sukabumi. The present study analyzed the preaching of Sanusi in the book Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’ and the authority of Sanusi which strengthened the Sundanese people to be guided by the tarekat Islam (the teachings of the Sufis' journey). By using qualitative methods and deductive analysis, this article aims to present Sanusi's response and the power of his Dakwah in Suni Sufism through his book Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’. The study found that on the one hand, the Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’ shows the renewal of the integration of Sufism studies at the community level, Pesantrens and several taklim assemblies in Sukabumi, West Java. On the other hand, the book becomes an important reference for Sunni tarekat learners, especially the Sundanese people in Sukabumi. Keywords: Ahmad Sanusi, Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’, Tasawuf Sunni. ABSTRAK Artikel ini memaparkan perjalanan K.H. Ahmad Sanusi dalam mempromosikan Tasawuf Sunni melalui kitabnya Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’ di wilayah Sukabumi, Jawa Barat. Dalam kitabnya, Sanusi tidak hanya fokus pada dakwah saja, namun ia juga menguatkan posisinya sebagai Ajengan Sunda yang mempengaruhi wacana Tasawuf Sunni di Sukabumi. Dengan menggunakan metode kualitatif dan analisis deduktif, artikel ini bertujuan untuk menghadirkan respon Sanusi dan kekuatan dakwahnya dalam Tasawuf Suni melalui kitabnya Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’. Tulisan ini menganalisa dakwah khasnya dalam kitab Sirāj al-Ażkiyā’ dan otoritas Sanusi dalam mengukuhkan masyarakat Sunda untuk berpedoman pada tarekat Islam. Temuan penelitian ini menunjukkan adanya pembaharuan dan integrasi kajian Tasawuf di tataran masyarakat, lembaga pesantren dan beberapa majelis taklim di Sukabumi, Jawa Barat. Sisi lainnya menunjukkan bahwa kitab Sirāj al-Ażkiyā’ menjadi referensi penting bagi pembelajaran tarekat Suni untuk masyarakat Sunda di Sukabumi. Kata kunci: Ahmad Sanusi, Sirāj al-Ażkiyā’ fī Tarjamah al-Azkiyā’, Tasawuf Sunni.